2004
DOI: 10.1111/j.1474-8673.2004.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Fructose overload modifies vascular morphology and prostaglandin production in rats

Abstract: 1. A fructose (Fru)-enriched diet induces a mild increase in blood pressure associated with hyperglycaemia, hypertriglyceridaemia, and insulin resistance, resembling the human 'syndrome X', being an useful model to study hypertension and type 2 diabetes. 2. A sustained elevation of blood pressure is associated with cardiovascular structural modifications such as left ventricular hypertrophy and increased wall thickness:lumen diameter ratio in blood vessels. 3. Prostanoids (PR), metabolites of arachidonic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…We demonstrated that in fructose-fed ApoE-KO mice, the media cross-section area from aortas and mesenteric arteries were significantly increased while lumen diameter was normal. This remodeling format is similar to that found in fructose-fed rats by Puyo et al [19]. …”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated that in fructose-fed ApoE-KO mice, the media cross-section area from aortas and mesenteric arteries were significantly increased while lumen diameter was normal. This remodeling format is similar to that found in fructose-fed rats by Puyo et al [19]. …”
Section: Discussionsupporting
confidence: 89%
“…In addition, direct exposure of human aortic endothelial cells to high glucose levels results in nitration of the PGI synthase enzyme and an impairment of prostacyclin release (8,34). Finally, PGI 2 and PGE 2 release was reported to be diminished in a fructose feeding model of elevated glucose levels (29). From these studies, we would hypothesize that endothelial dysfunction in OZR might, at least partly, result from the increased blood glucose and decreased insulin sensitivity present in these animals.…”
Section: Discussionmentioning
confidence: 93%
“…These substances have been implicated in increased peripheral resistance, which has been postulated as one of the mechanisms involved in fructose‐induced elevation of blood pressure. Moreover, an altered pattern of prostanoid release has been previously found in mesenteric vessels of experimental diabetic (Peredo et al ., ) and fructose‐treated rats (Puyó et al ., ).…”
Section: Introductionmentioning
confidence: 97%